2014
DOI: 10.1371/journal.pone.0098526
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Multiple Infection and Relatedness on Virulence: Disease Dynamics in an Experimental Plant Population and Its Castrating Parasite

Abstract: The level of parasite virulence, i.e., the decrease in host's fitness due to a pathogen, is expected to depend on several parameters, such as the type of the disease (e.g., castrating or host-killing) and the prevalence of multiple infections. Although these parameters have been extensively studied theoretically, few empirical data are available to validate theoretical predictions. Using the anther smut castrating disease on Silene latifolia caused by Microbotryum lychnidis-dioicae, we studied the dynamics of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 65 publications
0
17
0
Order By: Relevance
“…However, another factor may limit pathogen migration and contribute to the relative isolation among geographically‐circumscribed genetic clusters of the anther‐smut fungus. A competitive exclusion of distantly related genotypes by resident genotypes has been shown previously to occur in M. lychnidis‐dioicae (Hood, ; López‐Villavicencio et al ., , ; Buono et al ., ). This relatedness‐dependent competitive exclusion may prevent long‐distance migrants to establish in genetically different clusters.…”
Section: Discussionmentioning
confidence: 97%
“…However, another factor may limit pathogen migration and contribute to the relative isolation among geographically‐circumscribed genetic clusters of the anther‐smut fungus. A competitive exclusion of distantly related genotypes by resident genotypes has been shown previously to occur in M. lychnidis‐dioicae (Hood, ; López‐Villavicencio et al ., , ; Buono et al ., ). This relatedness‐dependent competitive exclusion may prevent long‐distance migrants to establish in genetically different clusters.…”
Section: Discussionmentioning
confidence: 97%
“…These fitness losses are much higher than those reported for anther‐smut on S. latifolia , where complete sterilization was less common (0–60% of all infections; Buono et al . ), and overwinter recovery was high (>60% Biere & Antonovics ). Indeed Rausher () calculated that the total loss in lifetime fitness of S. latifolia as a result of anther‐smut infection approximated the cost of resistance.…”
Section: Discussionmentioning
confidence: 99%
“…latifolia plants. The spatial structure found in populations (Giraud, ) would not explain the high relatedness among fungal strains within plants found in experimental inoculations (Buono, Lopez‐Villavicencio, Shykoff, Snirc, & Giraud, ; Koskella et al., ; López‐Villavicencio et al., ) but could still play a role in nature in increasing further relatedness within plants (Lopez‐Villavicencio et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Virulence was found to be higher for multiply infected plants than for singly infected ones, with more spores produced (and thus likely more host resource uptake by the pathogen), lower recovery probability and greater castration (Buono et al., ; Hood, ; López‐Villavicencio et al., ). However, higher castration rates in multiple infections were mitigated by greater relatedness (Buono et al., ; López‐Villavicencio et al., ). This indicated that the fungus behaved differently when competing with a close versus a distant relative within the same host plant.…”
Section: Introductionmentioning
confidence: 99%